2014
DOI: 10.1016/j.brainresbull.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Can fear extinction be enhanced? A review of pharmacological and behavioral findings

Abstract: There is considerable interest, from both a basic and clinical standpoint, in gaining a greater understanding of how pharmaceutical or behavioral manipulations alter fear extinction in animals. Not only does fear extinction in rodents model exposure therapy in humans, where the latter is a cornerstone of behavioral intervention for anxiety disorders such as post-traumatic stress disorder and specific phobias, but also understanding more about extinction provides basic information into learning and memory proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 151 publications
(178 reference statements)
3
84
0
Order By: Relevance
“…Additionally or alternatively, the improvement in this subgroup might not necessarily result from the added exposure but rather from the spacing of the additional exposure sessions during the booster phase. Animal studies (see Fitzgerald et al, 2014) showed that, once initiated in a massed way, extinction learning is boosted when subsequent trials are spaced (Cain et al, 2003). Third, the patients in this cluster may have needed exposure in a variety of contexts such as the home environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally or alternatively, the improvement in this subgroup might not necessarily result from the added exposure but rather from the spacing of the additional exposure sessions during the booster phase. Animal studies (see Fitzgerald et al, 2014) showed that, once initiated in a massed way, extinction learning is boosted when subsequent trials are spaced (Cain et al, 2003). Third, the patients in this cluster may have needed exposure in a variety of contexts such as the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…More theoretically, results from animal studies about fear extinction learning (i.e. the development of new associations with the stimulus that inhibits the manifestation of the original fear memory and the presumed mechanism of action of exposure therapy; see for an overview Fitzgerald, Seemann, & Maren, 2014) showed that once extinction learning is initiated in a massed way, further extinction learning is more effective when trials are spaced (Cain, Blouin, & Barad, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…A major limitation to long-term remission of anxiety disorders is the high relapse rate despite of effective psychological and pharmacological interventions (Yonkers, Bruce, Dyck, & Keller, 2003). Thus, relapse prevention may represent a good intervention point for improving long-term therapeutic efficacy, which has recently become a major focus of experimental and clinical research (Fitzgerald, Seemann, & Maren, 2014;Haaker et al, 2013;Kindt, Soeter, & Vervliet, 2009;Schiller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an inability to suppress or extinguish fear memories may sustain pathologically high levels of fear in patients with PTSD years after the trauma (1)(2)(3)(4)(5)(6). A variety of clinical interventions to facilitate fear extinction in patients with PTSD are currently being explored, although effective treatment for many afflicted individuals remains elusive (7,8).…”
mentioning
confidence: 99%